Simulated Pediatric Blood Cultures to Assess the Inactivation of Clinically Relevant Antimicrobial Drug Concentrations in Resin-Containing Bottles - Giordano, Liliana; Liotti, Flora Marzia; Menchinelli, Giulia; De Angelis, Giulia; D’Inzeo, Tiziana; Morandotti, Grazia Angela; Sanguinetti, Maurizio; Spanu, Teresa; Posteraro, Brunella (Frontiers in Cellular and Infection Microbiology, 2021)
The bacteremia level as well as the administration of antibiotics before blood collection may significantly affect the recovery of bacterial pathogens from pediatric blood cultures in BacT/Alert Virtuo or Bactec FX BC systems, which remain the common technique to diagnose bacteremia in pediatric patients. We simulated pediatric blood cultures with low or intermediate bacteremia level to evaluate BacT/Alert PF Plus and Bactec Peds Plus blood culture bottles for resin-based inactivation of 16 antibiotic-bacterium combinations. Overall, 105/192 (54.7%) of BacT/Alert PF Plus bottles and 69/192 (36.0%) of Bactec Peds Plus bottles allowed organisms to grow when exposed to antibiotics. In particular, both BacT/Alert PF Plus and Bactec Peds Plus bottles proved to be effective with piperacillin/tazobactam and Pseudomonas aeruginosa or with oxacillin and methicillin-susceptible Staphylococcus aureus (100% growth), whereas no effectiveness was apparent with ceftriaxone and Escherichia coli, Streptococcus agalactiae, or Streptococcus pneumoniae or with cefepime and E. coli (0% growth). In some relevant instances (e.g., with vancomycin and methicillin-resistant S. aureus or Streptococcus pneumoniae), BacT/Alert PF Plus bottles were superior to Bactec Peds Plus bottles. Together, these findings underscore the potentiality of resin-containing bottles to enhance diagnosis of bacteremia in pediatric patients on antimicrobial therapy. This is particularly true with one of evaluated BC systems and with simulated intermediate bacteremia level only.